Perceptual-vision training as a strategy for healthy aging in adults with intellectual disability: a study protocol - Luca Cavaggioni; Damiano Formenti; Paolo Castiglioni; Paolo Castiglioni; Luca Paolo Ardigò; Giampiero Merati; Giampiero Merati (Frontiers in Psychology)
Aging leads to changes in motor-cognitive performance. Despite the importance of physical activity for healthy aging and the need for health promotion interventions in individuals with intellectual disability (ID), there is a lack of empirically strategies for promoting health in adults with ID. Therefore, we are conducting a clinical trial (NCT06628999 on clinicaltrials.gov) to investigate a strategy for promoting healthy aging by targeting physical and cognitive domains in ID individuals. The present work aims to provide a detailed account of the study protocol of the proposed trial to promote transparency and dissemination of the ongoing research. Specifically, this project will study the effect of a vision training program on cognitive performance and physical fitness in adults with ID. A secondary aim is to examine the association between mental and physical performance outcomes. Participants will be randomly allocated into a vision training group (VT, n = 28), a vision training-detraining group (VTD, n = 28), and a control group (C, n = 28). During the first 8 weeks, the VT and VTD groups will follow the same training protocol (based on vision oculomotor exercises combined with postural control exercises). From weeks 9 to 16, the VT group will continue the training protocol, whereas the VTD group will abstain from training (detraining). Cognitive performance and physical fitness will be assessed at baseline, mid- and post-training intervention. Overall, a vision training program can positively impact various aspects of life for individuals with ID promoting autonomy, and social integration to counteract the aging process.